Penerapan Prinsip Kehati-hatian dalam Kebijakan Perlindungan dan Pengelolaan Lingkungan Hidup di Bidang Pertanian Untuk Keunggulan Varietas Produk Rekayasa Genetik - La Ode Angga Angga (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
Study the application of the precautionary principle in environmental protectionand management in agriculture for excellence varieties of genetically modified productsget answers: First; Ignoring the principle of prudence in Environmental Protection andManagement in the Regulation of the Minister of Agriculture Policy No. 61 /Permentan / OT.140 / 10/2011 on Testing, Assessment, Waiver and Withdrawalvarieties, there is a tendency to Regulation is made only for the sake of short-term andto mengakomudir interests of investors and entrepreneurs, as well as ignoring theprecautionary principle in the product of genetic engineering. The Second; Due toNeglect Law Precautionary Principle in Agricultural Policy Regulation No. 61 /Permentan / OT.140 / 10/2011, causing chaos or legal uncertainty, so the validityineffective and inefficient. The Third; Results Formulation Formulation of PolicyRegulation of the Minister of Agriculture No. 61 / Permentan / OT.140 /10/2011 on Testing, Assessment, Waiver and Withdrawal varieties responsive andaccommodating to the precautionary principle in environmental protection andmanagement in Indonesia, done with the precautionary principle as set out in Article 2fUUPPLH with description and Article 3 of Regulation No. 21 of 2005 and anexplanation, and as the implementation of the precautionary principle beforemelakukakn assessment activities, Waiver and Withdrawal varieties must pass theEIA, Environmental Permits and Environmental Risk Analysis.